2017
DOI: 10.3390/agronomy7040066
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Combined Effect of Tillage, Nitrogen Fertilization and Cover Crops on Nitrogen Use Efficiency in Winter Wheat

Abstract: A field study was conducted in northern France over two consecutive years to evaluate the combined effect of conventional tillage (CT) vs no till (NT) with or without cover crops (cc) and nitrogen (N) fertilization on various agronomic traits related to N use efficiency in winter wheat. Five years after conversion of CT to NT, significant increases in N use efficiency, N utilization efficiency, N agronomic efficiency, N partial factor productivity, N apparent recovery fraction and N remobilization were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…NUE was significantly higher when durum wheat was grown using NT. This result was in agreement with those obtained by Soon et al [41] and Habbib et al [42] who showed that for wheat, NUE was higher under NT compared to CT conditions. On the contrary, different results were obtained, when NUE was higher in CT soils due to an increase in yield [37,43] or due to N fertilizer immobilization through crop residues, and by an increase in fertilizer rates with NT [12].…”
Section: Agronomic Performancesupporting
confidence: 93%
“…NUE was significantly higher when durum wheat was grown using NT. This result was in agreement with those obtained by Soon et al [41] and Habbib et al [42] who showed that for wheat, NUE was higher under NT compared to CT conditions. On the contrary, different results were obtained, when NUE was higher in CT soils due to an increase in yield [37,43] or due to N fertilizer immobilization through crop residues, and by an increase in fertilizer rates with NT [12].…”
Section: Agronomic Performancesupporting
confidence: 93%
“…Within‐treatment crop yield and soil chemistry showed no significant differences during the last 2 years (2012 and 2013; Supporting Information Figure ), suggesting the system has reached an equilibrium and that sample plots simultaneously underwent only fluctuations of external factors over time (e.g., meteorology, atmospheric deposits) beside the investigated factors (i.e., N and CC). We thus assumed that, all else being equal, our comparative study only captured between‐treatments difference in terms of crop productivity, soil microbial diversity, soil nitrogen/carbon content (Habbib et al., ; Nivelle et al., ; Verzeaux et al., ; Verzeaux, Hirel, Dubois, Lea, & Tétu, ; Supporting Information Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…The two genotypes ('HD 3249' and 'HD 3117') with the greatest straw yield had N150 splits, which increased photosynthesis and dry matter output. The top dressing of wheat genotypes with the right dosage and timing of N may boost yields and HI [27][28][29][30]. The huge production discrepancies between the three N levels show that crop yields may be increased, particularly in plots with low N fertilization.…”
Section: Effects Of N Fertilization On Wheat Yields Harvest Index And...mentioning
confidence: 99%